Social robots as leaders: Leadership styles in human-robot teams - Lopes, S.; Rocha, J.; Ferreira, A. I.; Prada, R. (Procesdings of 2021 30th IEEE International Conference on Robot & Human Interactive Communication (RO-MAN), 2021)
This paper explores robotic leadership and the impact of different human-leadership styles in teams leaded by social robots. It is anticipated that social robots can have the capability to serve as leaders for human teams and to collaborate with humans in order to improve the organizational requirements of the workplace environment. We report an experiment conducted in order to determine which humanleadership styles would be associated with better results in organizational phenomena, such as, employee productivity, role ambiguity, engagement and employee satisfaction. The sample comprised 108 collaborators divided in 36 teams, who had to perform a collaborative task with a robotic leader acting according to two different leadership styles. The experiment results showed that both leadership styles can have positive impacts in organizational outcomes, although in different aspects. These findings yield important insights for the creation of robotic partners and for the successful introduction of robots as leaders of human teams